5‐year randomized multicenter clinical trial on single dental implants placed in the midline of the edentulous mandible. Issue 2 (26th December 2020) - Kern, Matthias; Behrendt, Christoph; Fritzer, Elfriede; Kohal, Ralf J.; Luthardt, Ralph G.; Maltzahn, Nadine Frfr. v.; Rädel, Michael; Reissmann, Daniel R.; Schwindling, Franz Sebastian; Wolfart, Stefan; Passia, Nicole
Abstract: Objectives: This multicenter randomized controlled clinical trial was conducted to investigate whether the loading protocol of single dental implants placed in the midline of edentulous mandibles will influence the implant survival or prosthetic maintenance. Materials and Methods: In total, 158 patients were randomly assigned either to the immediate loading group ( n = 81) or to the delayed loading group ( n = 77). All implants were loaded with an overdenture retained by a ball attachment. Results: After 5 years, 102 patients attended the follow‐up investigation. Immediately loaded single implants in the midline of the edentulous mandible revealed a statistically significant lower survival rate than implants loaded conventionally over an observation period of 5 years. In the immediate loading group, 9 implants failed within the first three months of implant loading. No further implant loss was recorded for this group. Two implants failed in the delayed loading group, whereas one implant had to be removed during second‐stage surgery and the second five years after implant loading. Non‐inferiority of the survival rate of the midline implant of the immediate loading group, compared with the delayed loading group, could not be shown ( p = .79, CI immediate loading: 74.9%; 100.0%, CI delayed loading: 73.0%; 100.0%). The observed difference in implant survival between the two treatment groups over time was statistically significant. Conclusions: The results of the present study indicate that immediate loading of a single mandibular implant in the edentulous mandible should be considered only in exceptional cases.